Handbook of Non-Motor Symptoms in Parkinson's Disease - Chaudhuri, K Ray.; Martinez-Martin, Pablo; Odin, Per.; Antonini, Angelo; SpringerLink (Online service) (Heidelberg : Springer Healthcare UK : Imprint: Springer Healthcare, 2011)
Handbook of Non-Motor Symptoms in Parkinson$1 (Bs Disease is designed to provide practical tips and emphasize key priorities for treatment of non-motor aspects of the disorder. The quick-reference handbook format, with key points highlighted by the use of figures and tables, will provide the reader with high-value practical information.s
Introduction -- The burden of non-motor symptoms -- Assessing non-motor symptoms: an overview of scales and questionnaires -- An in-depth look at the Non-Motor Symptom Scale -- Neuropsychiatric symptoms -- Sleep-related symptoms -- Bladder dysfunction -- Sensory symptoms -- Sexual symptoms -- Gastrointestinal symptoms -- Other symptoms.
Keywords: Medicine; Geriatrics; Gastroenterology; Neurology; Psychotherapy; Urology; Quality of Life; Quality of Life -- Research; Medicine & Public Health; Geriatrics/Gerontology.; Quality of Life Research; Gastroenterology; Urology/Andrology.; Neurology; Psychotherapy